Choose the best model for building life tables in Iraq - القزاز قتيبة نبيل; محمد ذو الفقار جاسم (Journal of Economics and Administrative Sciences, 2015)
Demography or population studies or demography is the science that is based on the different characteristics of the population scientific study, and represent a population studies principled way to understand the population of society, in addition to verification of the population in a given area determine the reason for the increase or decrease this number from the previous statistical As these studies estimate future trends for the occurrence of demographic change in terms of birth, death and migration That the registration of deaths of paramount importance narrated that way can the demographic reality of the population analysis, and coverage of the health authorities’ needs and enable government institutions of decision-making and do health procedures and meet the need for information about demographic changes in the past I have been in this research use 1997 census data to build a complete life tables using two methods (Elandt johson and method of Akima), by relying on the tables condensed life and used the method (Cole Demeny) built in, and perhaps the most important thing is concentrated upon research is to choose the best method of composition of by comparing life expectancy of the Central Bureau of Statistics according to the 1997 census with the way it turned out the method of Elandt johson using life tables Cole Demeny are the best